Laryngeal hamartoma: A case report - Ryuzaburo Higo; Masataka Kojima; Shin Itoh (Otolaryngology Case Reports, 2022)
A 49-year-old male, who complained of hoarseness was referred. A fiberscopic evaluation revealed a xanthic, polypoid mass on the right side of the larynx. Magnetic resonance imaging revealed a well-circumscribed mass, showing a relatively high signal in the T1-weighted image and high signal in the T2-weighted image. Under direct laryngeal microsurgery, the mass lesion at the right ventricle of the larynx was detected and excised successfully. Histopathological examination revealed a large amount of mature lipocytes and mature mucous glandular structures with normal stratified squamous epithelium. Neither mitotic nor atypical figures were observed. The pathology was mostly consistent with a hamartoma. The postoperative course was uneventful, and there have been no signs of recurrence for 4 years. Although hamartomas may occur in any organ, hamartoma of the larynx is quite rare and the number of reported cases is limited. Characteristics, differential diagnosis, and treatments of laryngeal hamartomas are also discussed.